Implementasi Konsep Stylish Homey Pada Interior House Of Cupcake di Surabaya - Jessika Erine Fandiyanto (Intra, 2013)
Popularity of cupcake in Indonesia starts from Bandung and endemic to other major cities. House Of Cupcake is a form of reaction to respond to these trends in Surabaya. House Of Cupcake is a place that is commercial, entertainment and education, aiming to make the cupcake as the cake is easy to obtain but still unique, as well as accommodate the cupcake connoisseurs and customers in particular in the city of Surabaya, which is one of the major cities in Indonesia. Design method using the approach of Michael J. French, where the results of the initial stages of the design will be used in the next stages, but can occur reciprocal to produce an appropriate design. Raised the concept is stylish homey, where the interior is to be created but the atmosphere of the house gets a touch of style commercial. This concept is applied in interior and decorative elements. Stylish homey is manifested through the choice of colors and a homey atmosphere raises the appropriate material.